Helical intensity‐modulated radiotherapy with concurrent chemotherapy for oropharyngeal squamous cell carcinoma: A prospective investigation of acute swallowing and toxicity patterns. Issue 9 (13th May 2018) - Moroney, Laura B.; Helios, Jennifer; Ward, Elizabeth C.; Crombie, Jane; Pelecanos, Anita; Burns, Clare L.; Spurgin, Ann‐Louise; Blake, Claire; Kenny, Lizbeth; Chua, Benjamin; Hughes, Brett G. M.
Abstract: Background: Conformal radiotherapy modalities may minimize treatment toxicities. The purpose of this study was to document the extent and timing of dysphagia and related toxicities during helical intensity‐modulated radiotherapy (IMRT) with chemotherapy for oropharyngeal squamous cell carcinoma (SCC). Methods: We conducted a prospective study of 76 patients with oropharyngeal SCC undergoing helical IMRT with chemotherapy. Dysphagia and acute toxicity data were collected weekly during treatment and at 2, 4, and 12 weeks posttreatment using the Functional Oral Intake Scale, diet descriptors, and Common Terminology Criteria for Adverse Events (CTCAE) version 4.0. Results: Patients experienced maximum incidence of grade 3 dysphagia (61%), mucositis (30%), and thick saliva (38%), with grade 2 xerostomia (87%) and dysgeusia (97%). Only 14.5% were nil‐by‐mouth. Symptoms peaked in week 7 and improved thereafter. Grade 3 dysphagia was twice as common for T3 to T4 tumors compared with T2. Conclusion: Results confirm that patients with oropharyngeal SCC undergoing helical IMRT with chemotherapy continue to experience incidences of acute toxicities comparable with other conformal techniques, and need supportive cares.